Synthesis and Characterization of Complexes of Thorium(IV) with Pyrrolidinobenzyl Benzamide and Various Anions - VISWANATHAN, M. (Asian Journal of Chemistry, 2010)
A series of complexes of Th(IV) with pyrrolidinobenzyl benzamide (PBB), a Mannich base derived from pyrrolidine, benzamide and benzaldehyde and various anions such as chloride, nitrate, acetate, thiocyanate and perchlorate have been synthesized and characterized. Their probable structures have been determined by elemental analysis, molar mass, conductivity, spectral, thermal and X-ray diffraction studies. The complexes exhibit the formulae : [Th(PBB)3X] where X = Cl–, NO3–, NCS–, CH3COO– or ClO4–. In these complexes the PBB acts as a bidentate ligand, whereas the monovalent anions act as unidentate ligands. The biological activities of the ligand and their metal chelates against E. coli, S. aureus, K. pneumoniae and P. aeruginosa were also studied. The complexes have higher activity than that of the free Mannich base.